SYSTEMATIC LITERATURE REVIEW: PENGARUH E-MODUL BERBASIS PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Fadhillah Raihana Putri; Andriani Simanjuntak; Jelita Sihombing; Mariati Purnama Simanjuntak (STKIP Subang, 2026)
This research is motivated by the low level of students' critical thinking skills, whichremains a challenge in learning, particularly due to the use of teacher-centeredlearning models that lack active student involvement. Therefore, learning innovationis needed through the use of teaching materials that support higher-order thinkingskills, one of which is Problem-Based Learning (PBL)-based e-modules. This studyaims to analyze the effect of PBL-based e-modules on students' critical thinkingskills through the Systematic Literature Review (SLR) method. Research data wereobtained from 20 national and international scientific articles published between2021 and 2025 and analyzed using qualitative descriptive techniques. The resultsof the study indicate that the use of PBL-based e-modules has a positive influenceon students' critical thinking skills at various levels of education. PBL-based emodules can increase students' activeness in identifying problems, analyzinginformation, and developing solutions logically and systematically. Furthermore, theintegration of e-modules with other approaches such as STEM and SocraticDialogue further strengthens the improvement of critical thinking skills. Thus, PBLbased e-modules can be an alternative innovative teaching material